Public preferences on written informed consent for low‐risk pragmatic clinical trials in Spain. (11th June 2017) - Dal‐Ré, Rafael; Carcas, Antonio J.; Carné, Xavier; Wendler, David
Abstract : Aims: Pragmatic randomized clinical trials (pRCTs) collect data that have the potential to improve medical care significantly. However, these trials may be undermined by the requirement to obtain written informed consent, which can decrease accrual and increase selection bias. Recent data suggest that the majority of the US public endorses written consent for low‐risk pRCTs. The present study was designed to assess whether this view is specific to the US. Methods: The study took the form of a cross‐sectional, probability‐based survey, with a 2 × 2 factorial design, assessing support for written informed consent vs. verbal consent or general notification for two low‐risk pRCTs in hypertension, one comparing two drugs with similar risk/benefit profiles and the other comparing the same drug being taken in the morning or at night. The primary outcome measures were respondents' personal preference and hypothetical recommendation to a research ethics committee regarding the use of written informed consent vs. the alternatives. Results: A total of 2008 adults sampled from a probability‐based online panel responded to the web‐based survey conducted in May 2016 (response rate: 61%). Overall, 77% of respondents endorsed written consent. In both scenarios, the alternative of general notification received significantly more support (28.7–37.1%) than the alternative of verbal consent (12.7–14.0%) ( P = 0.001). Forty per cent of respondents preferred and/or recommended general notification rather than written consent. Conclusions: The results suggested that, rather than attempting to waive written consent, current pRCTs should focus on developing ways to implement written consent that provide sufficient information without undermining recruitment or increasing selection bias. The finding that around 40% of respondents endorsed general notification over written consent raises the possibility that, with educational efforts, the majority of Spaniards might accept general notification for low‐risk pRCTs.